A modified and fast method for fixation and processing plant parasitic nematodes to anhydrous glycerin - WU Yang; LIU Bin; LIANG Ding-dong; JIANG Li-qin; ZHENG Jing-wu (浙江大学学报. 农业与生命科学版, 2006)
A modified method, which is simpler and faster than most of the traditional methods, for fixing and processing plant parasitic nematodes during their transform from water to glycerin, was provided on the basis of Seinhorst's work (1959). It was found that some of the important morphological characters, such as the shape of stylet, the incisures in lateral field and the bursa of males of tylenchoid nematodes, and the position of guiding ring, morphology of base of odontostyle, and the shape of tail of longidorid nematodes etc., were successfully maintained when specimens from Heterodera, Helicotylenchus, Hirschmanniella, Xiphinema and Longidorus were processed with the improved method.